PENGARUH MANAJEMEN LABA, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJKAN DEVIDEN DI BURSA EFEK INDONESIA (BEI) - Indra Abadi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
Financial functions that should be properly managed include: investment decisions, financing decisions, and dividend decisions. An optimal combination of these three factors will maximize the value of the firm which will further increase the prosperity for shareholders. The purpose of this study is to examine and analyze the effect of earnings management, profitability and liquidity on dividend policy. The type of research in this study is explanatory. Populations and samples at manufacturing companies listed on the Indonesia Stock Exchange 2014-2017. The sampling technique is purposive sampling. Quantitative data types and data sources used in the form of secondary data. Methods of data collection through literature study and documentation. Data analysis using SPSS version 22,0 The results showed that simultaneously there is influence between earnings management, profitability and liquidity to dividend policy (0,032 <0,05). However, partially found that: 1) earnings management has no effect on dividend policy (0,773> 0,005); 2) profitability influence to dividend policy (0,04 <0,05); 3) liquidity has no effect to dividend policy (0,966> 0,005 ).